Crisis of Society in Personal Life Stories (KULT_online, 2012)
Inspired by the flourishing autobiographical genre, the volume Autobiografie und historische Krisenerfahrung (Autobiography and Historical Crisis Experience) focuses on the interrelation between individual recollection in autobiographical forms and historical catastrophes and their narration. The interdisciplinary approach of the volume is reflected in its 18 contributions – written by researchers from literary and cultural studies, as well as by historians and scholars of film studies. The articles are assigned to three topical sections regarding the century of world wars, the end of the German Democratic Republic, and gender and generation. The study's subject is the memory of historical crises in autobiographical forms, constructed by narrative means. In the course of the analyses this proves to be fruitful, showing the coherence between the topoi mentioned in the title.